2015
DOI: 10.4238/2015.july.3.15
|View full text |Cite
|
Sign up to set email alerts
|

rbcS SRS4 promoter from Glycine max and its expression activity in transgenic tobacco

Abstract: ABSTRACT. The regulatory region of the ribulose-1,5-bisphosphate carboxylase small subunit gene SRS4 from soybean (Glycine max) was cloned using TAIL-PCR and general PCR, and named the rbcS promoter. The promoter was fused with the GUS gene and introduced into Nicotiana tabacum via Agrobacterium-mediated leaf disk transformation. In 4-week-old transgenic tobacco plants, the highest GUS expression levels were observed in the leaves, GUS activity was 7.13-and 7.40-fold higher in leaves than in stems and roots, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Green tissue specific promoters direct the expression preferentially in shoots and limit the expression in roots, where TI production is not needed. A previous study also showed similar gene expression patterns in leaves comparing 35S and rbcS-SRS4 promoter (Cui et al, 2015).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Green tissue specific promoters direct the expression preferentially in shoots and limit the expression in roots, where TI production is not needed. A previous study also showed similar gene expression patterns in leaves comparing 35S and rbcS-SRS4 promoter (Cui et al, 2015).…”
Section: Discussionsupporting
confidence: 63%
“…Each soybean TI gene was also cloned under the control of a green tissue-specific promoter. Soybean green-tissue specific promoter (1775 bp) of ribulose-1,5bisphosphate carboxylase small subunit gene SRS4 (rbcs-SRS4) (Cui et al, 2015) was amplified by PCR from soybean cv. 'Williams 82' using primers incorporating specific restriction enzymes (SacI and SpeI) (Supplementary Table S1).…”
Section: Expression Vector Constructionsmentioning
confidence: 99%
“…The soybean cultivar MON 87701-2 was produced by transfering the cry1Ac gene using a gene promoter rbcS4 control of the species Arabidopsis thaliana. This promoter expresses the characteristics of the gene of interest at high levels in green tissue (Cui et al 2015). The protein sequence is 99% identical to the Cry1Ac protein from B. thuringiensis kurstaki.…”
Section: Bt Soybeanmentioning
confidence: 93%
“…In this experiment, two Bt genes were constructed on a vector by utilizing the matrix attachment region (MAR) structure, applying different promoters (Cui et al, 2015) and enhancer sequences, and changing the open reading frame (ORF) sequence of exogenous genes. Four different types of vectors were constructed and transferred to tobacco, to obtain transgenic plants.…”
Section: Introductionmentioning
confidence: 99%